(untitled) (Kriminalističke teme, 2003)
This work, points to a number of hidden, not well known and insufficiently researched characteristics of planted fires and arsons that could be of crucial importance for research and discovery of relevant traces (material and immaterial indications) that point to the manner, causes/modus operandi and conditions that followed fires and/or arsons. Relevant criminal, criminological, protective and insurance- related characteristic of the “braking out” of fires and/or arsons are given schematically, as well as the key links between “causes” (that is the criminal “modus operandi”), “conditions” and “circumstances” that lead to planting of fires or malicious arsons. Attention is focused on the growing danger of easily accessible “know how”, hazardous substances and materials for criminal use in differently motivated attacks (ethnic, political or religious extremism/terrorism, material benefits or gains, psychological disturbances etc.) A more efficient criminological research and discovery of all relevant characteristic of such crimes would lead to faster and more effective preventive reactions and significant progress in the quality of the crime-related work, but would also lead to a breakthrough in many fields of fire and explosions prevention, protection and speedy intervention at all levels of responsibility, interest and non-profit interest.